2021
DOI: 10.1371/journal.pone.0253116
|View full text |Cite
|
Sign up to set email alerts
|

Government responses and COVID-19 deaths: Global evidence across multiple pandemic waves

Abstract: We provide an assessment of the impact of government closure and containment measures on deaths from COVID-19 across sequential waves of the COVID-19 pandemic globally. Daily data was collected on a range of containment and closure policies for 186 countries from January 1, 2020 until March 11th, 2021. These data were combined into an aggregate stringency index (SI) score for each country on each day (range: 0–100). Countries were divided into successive waves via a mathematical algorithm to identify peaks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 78 publications
4
115
0
Order By: Relevance
“…Finally, our study period ended in mid-June. Recent work has divided the COVID-19 pandemic in the USA into three waves, with the first wave running from late March 2020 until mid-June 2020 [ 71 ]. The exact day of June 12, 2020 was chosen because [ 1 ] enough cases had occurred in the US to obtain reliable estimates of laCFR by county and [ 2 ] it preceded CDC reopening guidance and a shift in reporting to the HHS Protect system, which is less readily available to the public than the prior CDC reporting system [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study period ended in mid-June. Recent work has divided the COVID-19 pandemic in the USA into three waves, with the first wave running from late March 2020 until mid-June 2020 [ 71 ]. The exact day of June 12, 2020 was chosen because [ 1 ] enough cases had occurred in the US to obtain reliable estimates of laCFR by county and [ 2 ] it preceded CDC reopening guidance and a shift in reporting to the HHS Protect system, which is less readily available to the public than the prior CDC reporting system [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis highlights the importance of considering time as a key factor, both to understand the causes and effects of the pandemic, and to design policies to address it; for example, it is relevant to assess governments’ interventions throughout the pandemic [ 24 ]. It also emphasizes the need to acknowledge the researchers’ methodological choices and their consequences in the results [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies of this period have generally found that both the overall stringency of NPIs and the speed of implementation contribute to reducing cases and deaths [ 1 , 12 , 22 – 23 ]. At the very least, the initial global response managed to steady what was, at that time, a rapidly accelerating pandemic.…”
Section: From Initial Convergence To Gradual Divergencementioning
confidence: 99%
“…Global transmission of the SARS-CoV-2 virus was first detected in January 2020, when cases outside of China were reported in France, Japan, Thailand, the USA and several other countries. Since then, over the course of the pandemic, almost every country in the world has experienced one or more waves of epidemic community transmission [1][2][3]. High levels of COVID-19 cases have threatened to overwhelm healthcare systems in many countries, and in some cases have collapsed them, compounding the infection fatality rate of the virus and causing high excessive mortality [4,5].…”
Section: Introductionmentioning
confidence: 99%